2018
DOI: 10.1007/s10570-018-1794-3
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose gelation in NaOH solutions is due to cellulose crystallization

Abstract: Cellulose gelation in 2 M NaOH aqueous solution was followed by time resolved turbidity and rheology measurements. The kinetics of gelation is observed to change from several hours down to few seconds when the temperature is increased from 25 to 30 °C, consistent with earlier work. The increase of turbidity upon gelation demonstrates the formation of larger cellulose aggregates, while wide angle X-ray scattering data confirms the gradual formation of crystalline domains. This suggests that the gelation can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…In particular, it is well known that the stability of cellulose solutions in aqueous alkali is strongly temperature dependent. The gelation time has been found to decrease exponentially with increasing temperature [64,65]. Nevertheless, the reason for such gelation is still not fully clear [21,[65][66][67].…”
Section: Rheological Analysis Of Cellulose Solution and Cellulose/mbamentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, it is well known that the stability of cellulose solutions in aqueous alkali is strongly temperature dependent. The gelation time has been found to decrease exponentially with increasing temperature [64,65]. Nevertheless, the reason for such gelation is still not fully clear [21,[65][66][67].…”
Section: Rheological Analysis Of Cellulose Solution and Cellulose/mbamentioning
confidence: 99%
“…The gelation time has been found to decrease exponentially with increasing temperature [64,65]. Nevertheless, the reason for such gelation is still not fully clear [21,[65][66][67]. Recently it has been suggested that the observed gelation is due to the precipitation of cellulose where the crystallites would then act as bridging points, competing for the same cellulose Polymers 2020, 12, 373 5 of 15 molecules, and thus acting as effective cross-linkers to form the 3D gel network [65].…”
Section: Rheological Analysis Of Cellulose Solution and Cellulose/mbamentioning
confidence: 99%
See 3 more Smart Citations